2014
DOI: 10.1371/journal.pone.0104936
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis Accuracy of PLA2R-AB in the Diagnosis of Idiopathic Membranous Nephropathy: A Meta-Analysis

Abstract: BackgroundThe presence of antibodies against the M-type phospholipase A2 receptor (PLA2R-AB) is considered to be a promising serological diagnostic biomarker of idiopathic membranous nephropathy (iMN). However, controversy remains about the diagnostic accuracy of serum PLA2R-AB testing. Here, we performed a comprehensive meta-analysis to assess the overall diagnostic value of serum PLA2R-AB testing in iMN detection.MethodsPubMed, Embase, and CNKI (Chinese National Knowledge Infrastructure) were searched for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 23 publications
3
81
1
12
Order By: Relevance
“…Because of the high specificity of aPLA2R for the diagnosis of MN [87], it is likely that in five years a kidney biopsy will no longer be required to diagnose MN in patients with detectable anti-PLA2R antibodies.…”
Section: Five-year Viewmentioning
confidence: 99%
“…Because of the high specificity of aPLA2R for the diagnosis of MN [87], it is likely that in five years a kidney biopsy will no longer be required to diagnose MN in patients with detectable anti-PLA2R antibodies.…”
Section: Five-year Viewmentioning
confidence: 99%
“…[20] Another similar study for PLA2R displayed 99% specificity and 78% sensitivity for the diagnosis of primary MN with tissue staining and serology distinguishing most cases of primary MN from secondary . [21] Larsen et al in his series of 85 primary MN and 80 secondary MN found sensitivity of 75% (95% CI: 65−84%) and specificity of 83% (95% CI: 72−90%). [14] Hence absence of circulating anti-PLA2R autoantibody at the time of kidney biopsy does not rule out a diagnosis of PLA2R-related MN.…”
Section: Performance Of Pla2r As Diagnostic Toolmentioning
confidence: 92%
“…In a recent meta-analysis including 2212 patients, specificity was 99% (95% CI: 96% to 100%) and sensitivity was 78% (95% CI: 66% to 87%) (48). Anti-PLA2R antibodies are neither found in other nephropathies and auto-immune diseases nor detected in healthy individuals.…”
Section: Translational Research In Membranous Nephropathymentioning
confidence: 94%